POLICYMAKING UNDER THE FIRE: THE US ASSAULT WEAPONS BAN POLICY - Gul, Zakir; Ulkemen, Sinan (European Scientific Journal, ESJ, 2013)
This paper explores and analyzes the banning policy of assault weapons (AWs) in 1994. Gun control has always been an important and debatable issue between the gun control advocates and gun right supporters in the US. In that regard, the main part is given to the gun control policy accomplished by the Clinton Administration in 1994. Further, several major theories and approaches in political science are used and applied to shed light on the issue and better understand the gun control policy. Some suggestions for new policy attempts of gun control were also made at the end of the study.